Gabriel Marcel se lewe en werk as agtergrond van sy nadering tot God, Deel 2 - Wolff, Ernst (Hervormde teologiese studies, 2000)
Gabriel Marcel,s life and work as background of his approach to God, Part 2. Having descibed Marcel's biography and the character of his thought, Part 2 of this essay continues by expounding the main themes of his philosophy. Firstly the nature and limits of human thought in relation to existence and being are explained. Secondly, closer attention is paid to participation. In the third section elements of Marcel's approach to God are sketched. The essay concludes with some critical comments.